The State Council's Jurisdiction to Develop the Disciplinary System - Salih, Saja; Qaddooi, Taghreed (Journal of Legal Sciences, 2026)
The special nature enjoyed by the rules of administrative law represented by the historical circumstances of its inception and the multiplicity of areas of administrative activity and its characterization as a rapidly developing law that exceeds the normal development in other laws, especially the laws of public service due to the development of administrative activity, had to be reflected in the laws governing the relationship between the employee and the state, including the Law on the Discipline of State and Public Sector Employees No. (14) of 1991 amended by Law No. (5) of 2008 , and that its amendment in 2008 by introducing some simple amendments does not live up to the level of development of the activity of the administration and the direction of the constitutional legislator in accordance with the Constitution of Iraq for the year 2005, in addition to the fact that the legal rules related to the discipline of employees are inevitably marred by deficiency as a humanitarian work is not characterized by perfection and its generality, especially with regard to procedures and guarantees of administrative investigation and disciplinary violations, opening the door to a developmental role played by the State Council.